THE NEW IBAN BILEK-FAMILY STRUCTURE: A THREAT OR THE DYNAMICS OF OUR TIME - Seidelson, Lucy Sebli (JURNAL MELAYU SEDUNIA, 2021)
This article aims to explore the impact of female-headed families on the Iban traditional bilek family structure. Hence, our study and data tend to stipulate that the increasing number of single mothers among the Iban is more likely or inevitably affect [if not] change the traditional structure of the bilek-family. In essence, the traditional family was previously absolute patriarchal in nature in terms of the hierarchical position and decision-making have continued to witness dynamic changes in the social realities. Accordingly, the absence of males as head of the family within this new form of bilek will further impact the role(s) and responsibilities that some contemporary Iban women are forced to shoulder. This study employed an ethnographic approach as a methodology because of the nature of the research. Snowball sampling was used as a sampling technique due to the challenges of identifying the participants for the study.